Does MacIntyre's Moral Sociology Presuppose a Personalist Moral Psychology? MacIntyre and Tomasello on Moral Psychology - Bernacchio, Caleb (Frontiers in Communication, 2022)
Alasdair MacIntyre has developed a theory of virtue ethics that is closely integrated with sociology and organization studies. While rejecting reductive views of the virtues, MacIntyre appeals to their functional role in facilitating collaboration as a basis for justifying their normative requirements. This raises the question of how agents within cooperative contexts come to appreciate their intrinsic value. I argue that MacIntyre’s account of the virtues is undergirded by an implicit personalist moral psychology. To make this evident, I draw upon the account of moral psychology developed by Michael Tomasello, who argues that a sense of moral obligation is generated when persons engage in collective action. Tomasello’s account complements MacIntyre’s by explaining how participation in social practices generates a sense of moral obligation but it does not address the problem of relativism. As a result, it does not fully explain how and why participants in practices come to see themselves as bound by moral norms since the threat of relativism undermines the idea that moral norms are binding. This limitation further illustrates the role of a personalist moral psychology in MacIntyre’s work: through the experience of cultural breakdown persons are able to view themselves as engaged in a shared inquiry concerning the good that transcends any specific culture. This provides the basis for a self-conscious sense of moral obligation that is not threatened by relativism.